Synthesis and modeling perspectives of rhizosphere priming. Issue 1 (19th August 2013) - Cheng, Weixin; Parton, William J.; Gonzalez‐Meler, Miquel A.; Phillips, Richard; Asao, Shinichi; McNickle, Gordon G.; Brzostek, Edward; Jastrow, Julie D.
Summary: The rhizosphere priming effect (RPE) is a mechanism by which plants interact with soil functions. The large impact of the RPE on soil organic matter decomposition rates (from 50% reduction to 380% increase) warrants similar attention to that being paid to climatic controls on ecosystem functions. Furthermore, global increases in atmospheric CO2 concentration and surface temperature can significantly alter the RPE. Our analysis using a game theoretic model suggests that the RPE may have resulted from an evolutionarily stable mutualistic association between plants and rhizosphere microbes. Through model simulations based on microbial physiology, we demonstrate that a shift in microbial metabolic response to different substrate inputs from plants is a plausible mechanism leading to positive or negative RPEs. In a case study of the Duke Free‐Air CO2 Enrichment experiment, performance of the PhotoCent model was significantly improved by including an RPE‐induced 40% increase in soil organic matter decomposition rate for the elevated CO2 treatment – demonstrating the value of incorporating the RPE into future ecosystem models. Overall, the RPE is emerging as a crucial mechanism in terrestrial ecosystems, which awaits substantial research and model development.   Contents     Summary 31 I. Introduction 31 II. Magnitude and driving variables of the rhizosphere priming effect 32 III. Will global environmental change alter the RPE? 34 IV. A game theoretic model: is priming the result of evolutionarily stable strategies? 35 V. A microbial physiology‐based model: simulating positive and negative RPEs 37 VI. A case study: matching simulation results with observations at the Duke FACE 38 VII. Research needs and future perspectives 39   Acknowledgements 41   References 41